Optimizing ECG Audits: Clustering-Based Identification of Ambiguous Exams - Rigueira, Pedro B.; Evangelista, Guilherme H. G.; Porfírio, Luisa G.; Grossi, Caio Souza; Buzelin, Arthur; Pappa, Gisele L.; Paixão, Gabriela M. M.; Ribeiro, Antonio; Meira Jr., Wagner (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2024: Anais do XXI Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2024.245283, 2024)
Electrocardiograms (ECG’s) are crucial tools for diagnosing heart diseases, and regular audits of these exams are essential to maintain diagnostic consistency, ensure quality standards, and secure the reliability of medical databases. However, the current practice of randomly selecting ECG’s for audit can be inefficient, as it often includes cases with clear, uncontroversial diagnoses. In this paper, we present an unsupervised method that uses clustering techniques to identify ECG’s with a higher likelihood of diagnostic ambiguity. Our approach identifies a group of exams with an average ambiguity rate of 38,98%, which is over three times higher than the 12% observed in conventional audit methods.